INTRODUCTION - L Sutton (Acta Theologica)
Devoting one’s life to the study of the Old Testament is to walk on a never-ending path that becomes a lifelong journey. A path that is illuminated by an array of literature on Law (and its narrative), History, Prophets, Wisdom, and Psalms. A journey that will keep on going, a truly “never-ending story”.